2013 IEEE Congress on Evolutionary Computation 2013
DOI: 10.1109/cec.2013.6557597
|View full text |Cite
|
Sign up to set email alerts
|

A novel mathematical modeling approach to the electric dispatch problem: Case study using Differential Evolution algorithms

Abstract: Nowadays, the population growth and economic development causes the need for electricity power to increase every year. An unit dispatch problem is defined as the attribution of operational values to each generation unit inside a power plant, given some criteria to be obeyed like the total power to be generated, operational bounds of these units etc. In this context, an optimal dispatch programming for hydroelectric units in energy plants provides a bigger production of electricity to be generated with a minima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 8 publications
(12 reference statements)
1
12
0
Order By: Relevance
“…As a computational simulation test, this paper proposes as test scenario a HPP in Brazil with nominal installed capacity of 396M W . The HPP has in its powerhouse 6 The first experiment aims to compare and to analyse the value found in monoobjective approach proposed by Marcelino [5] (the solution was found via a Differential Evolution algorithm [14]) and results found in proposed multiobjective approach. The second experiment aims to assess Pareto front quality obtained by NSGA-II and SPEA-II algorithms.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…As a computational simulation test, this paper proposes as test scenario a HPP in Brazil with nominal installed capacity of 396M W . The HPP has in its powerhouse 6 The first experiment aims to compare and to analyse the value found in monoobjective approach proposed by Marcelino [5] (the solution was found via a Differential Evolution algorithm [14]) and results found in proposed multiobjective approach. The second experiment aims to assess Pareto front quality obtained by NSGA-II and SPEA-II algorithms.…”
Section: Methodsmentioning
confidence: 99%
“…Marcelino [5] proposed a new mathematical model to solve HPP energy dispatch problem using DE. He showed that evolutionary strategy DE/best/1/bin is the most efficient for solving the mono-objective version of this problem.…”
Section: State Of the Artmentioning
confidence: 99%
See 3 more Smart Citations